2018
DOI: 10.14738/abr.610.5419
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Banking: evidence from Portugal

Abstract: The paper intends to empirically examine the motivators that influence consumers' intentions to use Mobile Banking in Portugal. The data was analyzed by employing exploratory as well as confirmatory analysis and a Structural Equation Model was extracted from 172 Portuguese respondents. The findings indicate that Portuguese consumers still prefer Online Banking rather than Mobile Banking. The Structural Equation model indicates that 'Perceived ease of use' and 'Perceived Usefullness' were the primary determinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…On the contrary, incorrect information, lack of transparency, and the perception that banking products and services have some financial, security, and privacy risk, especially in online transactions and in the oldest clients, could dramatically reduce using electronic banking services and bank cards. (Fragata et al, 2018;Mohammad, 2012;Arif et al, 2020;Dixit & Datta, 2010;Zheng et al, 2012;Khalid et al, 2013). Wang & Lin (2019) found that in contactless bank cards, individuals' security and privacy risk during use reduces their use and trust in these products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the contrary, incorrect information, lack of transparency, and the perception that banking products and services have some financial, security, and privacy risk, especially in online transactions and in the oldest clients, could dramatically reduce using electronic banking services and bank cards. (Fragata et al, 2018;Mohammad, 2012;Arif et al, 2020;Dixit & Datta, 2010;Zheng et al, 2012;Khalid et al, 2013). Wang & Lin (2019) found that in contactless bank cards, individuals' security and privacy risk during use reduces their use and trust in these products.…”
Section: Literature Reviewmentioning
confidence: 99%